Evaluation Method of Shale Brittleness Based on Multiple Influencing Factors - CHEN Wei; CHANG Xiaolong; LI Zhe; XIE Junyu; XU Shengchi; XIONG Yuwei (Cejing jishu)
The brittleness evaluation of shale reservoirs serves as a crucial basis for scientifically conducting fracturing operations and evaluating wellbore instability technologies. To scientifically and rapidly assess shale brittleness, this study focuses on the Paleogene Funing formation II member reservoirs in the Qutang Subsag of the Hai'an Sag, Subei basin. Starting from the factors influencing shale brittleness, a comprehensive evaluation model for shale brittleness is constructed based on the analytic hierarchy process, encompassing five dimensions: mineral composition, pore structure, organic matter content, formation temperature, and thermal maturity. In this comprehensive evaluation model, the factors influencing brittleness, in descending order of importance, are mineral composition, thermal maturity, total organic carbon content, formation temperature, and porosity, with respective weights of 0.423 7, 0.270 7, 0.168 6, 0.068 5 and 0.068 5. By comparing the evaluation results of the comprehensive shale brittleness evaluation model and four single-factor brittleness evaluation models with actual brittleness indices, it is demonstrated that the proposed model exhibits the lowest error compared to actual brittleness indices, enabling accurate assessments of shale reservoir brittleness. This model quantifies the weights of various influencing factors and features a straightforward calculation method, providing significant guidance for field operations.